2014
DOI: 10.1007/s13277-014-2779-y
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan up-regulated vascular endothelial growth factor (VEGF) expression and promoted angiogenesis in colon cancer

Abstract: Biglycan is an important component of the extracellular matrix, which belongs to the small leucine-rich proteoglycan family. Recent studies have shown that biglycan expression is elevated in many tumor tissues and implies poor prognosis, such as colon cancer. However, the molecular mechanism of biglycan in colon cancer has not been investigated. The present study aimed to investigate the effects of biglycan on vascular endothelial growth factor (VEGF) expression in colon cancer cells and on tumor angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…Interestingly, NF‐kB is an essential component in the TLR signaling pathway (Xiao and Ghosh, 2005). Studies have shown that BGN can upregulate VEGF expression and promote angiogenesis in colon cancer (Xing et al., 2015), which is consistent with our previous findings that BGN could stimulate tubular formation activity in HUVECs. Nevertheless, the exact mechanism through which BGN regulates VEGF expression remains unclear.…”
Section: Introductionsupporting
confidence: 93%
“…Interestingly, NF‐kB is an essential component in the TLR signaling pathway (Xiao and Ghosh, 2005). Studies have shown that BGN can upregulate VEGF expression and promote angiogenesis in colon cancer (Xing et al., 2015), which is consistent with our previous findings that BGN could stimulate tubular formation activity in HUVECs. Nevertheless, the exact mechanism through which BGN regulates VEGF expression remains unclear.…”
Section: Introductionsupporting
confidence: 93%
“…These results were consistent with previously published results, which demonstrated that biglycan may promote cell proliferation and the migratory abilities of cells (25,26). Furthermore, these results indirectly support our previous findings that biglycan overexpression promoted xenograft colon tumor growth, and that the upregulation of biglycan was associated with the malignancy in human colorectal cancer (13,27). The results of the present study indicated that biglycan has an oncogenic role in the colon cancer process, which is associated with regulating the proliferation, migration and invasion of colon cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…ECM reorganization is strongly interlinked with angiogenesis and related proteins were found regulated in both cell types as well. Biglycan is a structural component of the ECM but also contributes to blood vessel remodeling, apparently being able to upregulate the expression of VEGF and thus promoting angiogenesis (55). Indeed, this protein, when proteolytically released from the ECM, acts as a danger signal stimulating pro-inflammatory signaling and activating the inflammasome (56).…”
Section: Discussionmentioning
confidence: 99%